Suppression of SDP1 Improves Soybean Seed Composition by Increasing Oil and Reducing Undigestible Oligosaccharides - Aznar-Moreno, Jose A.; Mukherjee, Thiya; Morley, Stewart A.; Duressa, Dechassa; Kambhampati, Shrikaar; Chu, Kevin L.; Koley, Somnath; Allen, Doug K.; Durrett, Timothy P. (Frontiers in Plant Science, 2022)
In developing soybean seeds, carbon is partitioned between oil, protein and carbohydrates. Here, we demonstrate that suppression of lipase-mediated turnover of triacylglycerols (TAG) during late seed development increases fatty acid content and decreases the presence of undigestible oligosaccharides. During late stages of embryo development, the fatty acid content of soybean seed decreases while the levels of the oligosaccharides raffinose and stachyose increase. Three soybean genes orthologous to the Arabidopsis lipase gene SUGAR-DEPENDENT1 (SDP1) are upregulated at this time. Suppression of these genes resulted in higher oil levels, with lipid levels in the best lines exceeding 24 % of seed weight. In addition, lipase-suppressed lines produced larger seeds compared to wild-type plants, resulting in increases of over 20% in total lipid per seed. Levels of raffinose and stachyose were lower in the transgenic lines, with average reductions of 15% in total raffinose family oligosaccharides observed. Despite the increase in oil, protein content was not negatively impacted and trended higher in the transgenic lines. These results are consistent with a role for SDP1 in turning over TAG to supply carbon for other needs, including the synthesis of oligosaccharides, and offer new strategies to further improve the composition of soybean seeds.